Analysis of product innovation performances in terms of competitive strategies of companies in production sector under the influence of technology orientation - Çelikyay, Mehmet; Adıgüzel, Zafer (Canadian Institute For Knowledge Development, 2019)
Innovation is considered to be one of the most important research areas in the field of science and technology policies in recent years and it is seen as the main driving force of economic growth and welfare increase. In today's competitive global economy, a firm's product innovation capability determines its competitiveness and effectiveness in national or international production and trade networks. Companies that follow a cost leadership strategy can mainly compete at a lower price, which they can do by reducing their costs through efficient resource/production/distribution and scale economies The sustainability of the companies in this competitive environment with sustainable profitability depends on the determination of the competitive strategies to be put into practice and the strategy they implement in the most rational way. In this study, 383 white collar (engineer) employees were surveyed. The factor analysis (explanatory and confirmatory) and reliability analysis of the scales was conducted using SPSS 25 and AMOS Program. The correlation and regression analysis, and sobel and Hayes process tests were performed to examine the effect of mediator variable. The results showed that there is a statistically positive and meaningful relationship between technology orientation and product innovation. In addition, it was found that the cost leadership and differentiation strategies have a mediation effect in this relationship.
Keywords: Technology Orientation; Competitive Strategies; Cost Leadership Strategies; Differentiation Strategies; Product Innovation